Expert Validation: College Student Online Shopping Questionnaire (Docentes 2.0 Journal, 2022)
In recent years, e-commerce has generated a growing interest in our society. This marketing method was highly influenced by the COVID-19 pandemic and became more relevant, especially in the Z generation. This paper aims to expose how expert content validation was performed on an instrument to quantify university students' perceptions of online shopping. The research was based on the deductive, positivist paradigm, quantitative approach, non-experimental design, exploratory and cross-sectional type. Five experts participated, who were selected according to their theoretical and practical experience in the field of e-commerce. Microsoft Excel software was used in the elaboration of the experts' evaluation template, as well as in the calculation of the statistical indexes. The scores issued were analyzed with the Lawshe test modified by Tristan. According to the results, the proposed questionnaire is well-targeted in its objective. However, it is necessary to implement the adjustments indicated by the experts before proceeding with the subsequent phases of the construction process of this instrument. This paper presents the systematic application of a procedure to validate the content of a questionnaire. However, it should be considered that only five experts participated; also, the K-index was calculated based on their reported data. Future work could involve more experts. Once the final instrument has been defined, it could be applied to a pilot sample, and the statistical criteria for each question could be evaluated.
Keywords: Online shopping; university students; questionnaire; expert validation